The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.apenergy.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergent synchronisation properties of a refrigerator demand side management system

Abstract: In order to analyse the possibilities of improving grid stability on island systems by local demand response mechanisms, a multi-agent simulation model is presented. To support the primary reserve, an under-frequency load shedding (UFLS) using refrigerator loads is modelled. The model represents the system at multiple scales, by recreating each refrigerator individually, and coupling the whole population of refrigerators to a model which simulates the frequency response of the energy system, allowing for cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Concerns that frequency-responsive TCLs controlled by deterministic rules will exhibit herding behaviour and create frequency oscillations have been raised in various previous works, either by predictions or examples from simulations [13,21,22,25,[30][31][32]. The simplicity of our model allows for a rigorous mathematical treatment of the stability of a population of TCLs responding according to the scheme introduced above.…”
Section: Stability Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Concerns that frequency-responsive TCLs controlled by deterministic rules will exhibit herding behaviour and create frequency oscillations have been raised in various previous works, either by predictions or examples from simulations [13,21,22,25,[30][31][32]. The simplicity of our model allows for a rigorous mathematical treatment of the stability of a population of TCLs responding according to the scheme introduced above.…”
Section: Stability Analysismentioning
confidence: 98%
“…A number of simulations in the literature indicate TCL synchronisation following a frequency disturbance, for example, [13,21,22,25,[30][31][32]. As a result, various control schemes have been proposed that aim to prevent such behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…This paper shows the importance of desynchronizing the operation of a group of refrigerators in order to limit the payback load after the DR event that could cause severe peak power demand. The issue of synchronization is also shown in [21], where a frequency based demand side management strategy is applied to a cluster of refrigerators. [22] illustrates a strategy to manage at large scale the load of domestic refrigerators in order to reduce peak energy demand.…”
Section: Demand Responsementioning
confidence: 99%
“…Whilst control and protection devices on power system networks can work to minimize power fluctuations, synchronization could compromise the stability of the grid and increase network failure risks [18,19]. For small groups of domestic refrigerators, computationally demanding stochastic decentralized control has been proposed to ameliorate the effects of these power oscillations [20][21][22]. Initial studies suggested that networks of refrigerators can trigger sequential under-frequency events particularly after switching off and return to operation [23].…”
Section: The Extent Of the Challengementioning
confidence: 99%